Factori care favorizează un parcurs şcolar pozitiv - Vasile, Marian (Calitatea Vieții, 2011)
This paper approaches, in an exploratory manner, data gathered during the project “Un sprijin necesar pentru elevii de etnie roma şi turcă din judeţul Constanţa” thru eight focus groups with teachers from levels I–VIII, eight focus groups with parents and interviews with school principals. Beside the beneficiary of this research, the school from Medgidia, there were also included other schools: two from Bucharest and one from each of Medgidia, Buhuşi, Bacău and Piteşti. The discussions, focused on the identification of the factors that are unfavorable for school participation and favorable to school dropout, show the necessity to pay attention to the multiplication of the job opportunities for parents, enhancing the relationship between teachers and parents, using alternative educational programs inside (after school) or outside the school. Data suggests some future research directions: testing for the emergence of an “indifference culture toward education” and the “minority effect”.